Current and Future Challenges of Nanomaterials in Solar Energy Desalination Systems in Last Decade - GAJBHIYE, TRUPTI; SHELARE, SAGAR; Aglawe, Kapil (Transdisciplinary journal of engineering & science, 2022)
Renewable energy plays key role in developing any nation. Freshwater is sometimes hard to get to in places that are far aside or poor. Because of this, it is important to have a cheap and effective desalination system that helps these communities grow and helps society as a whole. For example, the development of nanotechnology could help solve water problems by making it easier to get rid of viruses, bacteria, and other contaminants and lowering the cost of purification processes. Desalination is a process that uses a lot of energy and is responsible for most of the costs of running the plant. Also, a lot of the power comes from the greenhouse gas emissions and traditional fossil-fuel-fired power plants which pose a serious danger to ecosystem. In the last few years, many studies have been done on the use of nanotechnology in desalination, the treatment of brine, and the role of renewable energy in desalination. The main goal of this paper is to look at the most important new developments in desalination nanotechnology with respect to energy. Some conclusions and suggestions for future research are made based on the progress made and the problems that still need to be solved.